Platelets: Novel Biomaterials for Cancer Diagnosis and Therapeutic Delivery - Wang, Xin; Chen, Jie; Shi, Hubing (MedComm - Biomaterials and applications, 2025)
ABSTRACT Platelets play a pivotal role in cancer detection and metastasis, serving both as novel liquid biopsy biomarkers and as versatile carriers in nanomedicine. Tumor‐educated platelets (TEPs) undergo molecular alterations influenced by the tumor microenvironment, with their RNA profiles—including mRNA, circular RNA, and long noncoding RNA—offering potential for early cancer detection, prognosis, and treatment monitoring. Additionally, platelet‐derived extracellular vesicles (PEVs) and activation markers (e.g., P‐selectin, CD40L) further enhance their diagnostic utility. However, standardization of platelet biomarker analysis remains a challenge for clinical implementation. Concurrently, nanotechnology is leveraging the natural biocompatibility and targeting properties of platelets to develop platelet‐based drug delivery systems and bioinspired nanomaterials, improving therapeutic precision and efficacy. Moreover, artificial intelligence (AI)‐driven biomarker analysis is refining TEP and PEV profiling, accelerating advances in precision oncology. Future research should focus on establishing standardized protocols, optimizing platelet‐based nanomedicine, and integrating AI to enhance diagnostic accuracy and therapeutic efficacy. By bridging biological insights with clinical applications, platelets hold significant promise as transformative tools in precision oncology. Platelets, particularly tumor‐educated platelets (TEPs), play a crucial role in cancer diagnosis and treatment. TEPs undergo molecular changes in RNA and protein profiles, making them valuable biomarkers for diagnosis, prognosis, and monitoring. In nanomedicine, platelets serve as drug carriers in tumor‐targeted nanomaterials, enhancing specificity and accuracy. Integrating liquid biopsy with nanotechnology offers promising potential in precision oncology.